2004
DOI: 10.1007/s00125-004-1407-6
|View full text |Cite
|
Sign up to set email alerts
|

11?-Hydroxysteroid dehydrogenase Type 1: genetic polymorphisms are associated with Type 2 diabetes in Pima Indians independently of obesity and expression in adipocyte and muscle

Abstract: Aims/hypothesis. The enzyme 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) modulates tissuespecific glucocorticoid concentrations by generating active cortisol. We have shown that adipose tissue 11β-HSD1 mRNA levels were associated with adiposity and insulinaemia. Here we conducted further expression and genetic association studies in Pima Indians. Methods. The 11β-HSD1 mRNA concentrations were measured in abdominal subcutaneous adipocytes (n=61) and skeletal muscle tissues (n=64). Single nucleotide polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
1
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 49 publications
3
92
1
6
Order By: Relevance
“…In two populations, polymorphisms were associated with an increased risk of diabetes and hypertension, but not obesity (38,39). A polymorphism was also found that predicts lower 11βHSD1 expression and protection against diabetes (40).…”
Section: Human Studiesmentioning
confidence: 89%
“…In two populations, polymorphisms were associated with an increased risk of diabetes and hypertension, but not obesity (38,39). A polymorphism was also found that predicts lower 11βHSD1 expression and protection against diabetes (40).…”
Section: Human Studiesmentioning
confidence: 89%
“…Further, human 11 -HSD1 mRNA levels did not correlate with any metabolic parameters, unlike adipose 11 -HSD1 in obese PIMA Indians (Nair et al, 2004). However, a number of studies have highlighted the importance of skeletal muscle as a potential site of activity of the enzyme in humans (Whorwood et al, 2001, Abdallah et al, 2005, Jang et al 2006, 2007 which may reflect a species difference.…”
Section: Other Important Sites Of 11 -Hsd1 Expressionmentioning
confidence: 93%
“…Polymorphisms of HSD11B1 were reported to be associated with type 2 diabetes and insulin resistance in Pima Indians [17]. However, several other studies have failed to find evidence of an association between HSD11B1 polymorphisms and type 2 diabetes, obesity, or metabolic syndrome [18][19][20][21].…”
Section: Laboratory Analysismentioning
confidence: 99%
“…Two SNPs in the HSD11B1 gene [IVS3-29G/T (rs12086634) in intron 3 and IVS4-11120A/G (rs1000283) in intron 5] and two SNPs in the H6PD gene [R453Q (rs6688832) and P554L (rs17368528) in exon 5] were analyzed. We selected these four SNPs after consulting previously published studies suggesting a positive association of these SNPs with metabolic disease [17,26,27] and reviewing the allele frequencies of the Asian population and locations using the international HapMap project (http://www.hapmap.org/). LD coefficient r 2 between rs12086634 and rs1000283, and rs6688832 and rs17368528 were 0.00 and 0.62 respectively (http://www.broad.mit.edu/mpg/haploview/).…”
Section: Dna Extraction and Genotypingmentioning
confidence: 99%